The Breadth, Freeness, and Yet Exclusiveness of the Gospel - Hoare, Edward, 1812-1894 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Breadth, Freeness, and Yet Exclusiveness of the Gospel" by Edward Hoare is a theological essay written in the 19th century, specifically during the Victorian era. This work delves into the fundamental truths of the Christian Gospel, examining its expansive nature as well as its exclusive aspects. The author seeks to clarify misconceptions about the Gospel's reach and scope, addressing criticisms that label it as narrow-minded while affirming its universal invitation for salvation. In this essay, Hoare argues for the broad and free nature of the Gospel, emphasizing that it is available to all humankind, regardless of nationality, ecclesiastical order, or doctrinal understanding. He asserts that the Gospel, rooted in the love of God, invites everyone to partake in salvation without limitations. However, he also highlights the exclusive aspect of the Gospel, proclaiming that salvation is found only through faith in Jesus Christ, as there is no other name by which people can be saved. Throughout the text, Hoare encourages readers to recognize the balance between the offers of grace and the necessity of belief, ultimately reinforcing the idea that while the Gospel is an open invitation, it remains anchored in the singular truth of Christ's salvific role. (This is an automatically generated summary.)
Release date is 2016-07-25
Transcribed from the [1865] William Hunt and Company edition by David Price
Keywords: Bible. Gospels -- Criticism, interpretation, etc